Planning with care complexity: Factors related to discharge delays of hospitalised people with disability. (26th July 2022) - Foster, Michele M.; Borg, David N.; Houston, Vivien; Ehrlich, Carolyn; Harre, Donna; Lau, Geoffrey; Geraghty, Timothy J.
Abstract: Planning for discharge and supports beyond hospital for people with disability in Australia involves negotiation of complex care systems. The aims of this study were to examine how the individualised support pathway of the National Disability Insurance Scheme (NDIS) functioned for admitted people with disability who required funded support to leave hospital; and to explore the factors indicative of increased care complexity associated with delays. Retrospective chart reviews of people with disability were conducted. Data on 198 eligible patients were extracted, including NDIS plan approval and plan implementation timeframes and discharge delay. Participants' median age was 52 years (interquartile range = 41–59). The most common disability type was spinal cord injury (41%). The median NDIS plan approval and implementation timeframes were 89 days (63–123) and 39 days (8–131), respectively, and most participants (72%) experienced a delayed discharge. A longer plan implementation timeframe was associated with higher odds of a delay in discharge (OR = 3.41, 95% credible interval = 1.56, 7.11). We did not find any evidence that plan approval timeframe, or any other variable indicative of increased care complexity, was associated with discharge delays. Our findings suggest that a delayed discharge will likely be the reality for people with disability who require funded supports to leave hospital. They also suggest that NDIS plan implementation is a major challenge and a focus for policy and practice improvements. To target solutions, further research should focus on the interactions and negotiations of the multiple intermediaries involved and resource and structural impediments to plan implementation.